2007
DOI: 10.1002/ajp.20482
|View full text |Cite
|
Sign up to set email alerts
|

Survey and comparison of major intestinal flora in captive and wild ring‐tailed lemur (Lemur catta) populations

Abstract: A survey to identify the major intestinal species of aerobic bacteria, protozoa and helminths was conducted on captive and wild populations of ring-tailed lemurs (Lemur catta). Samples were collected from 50 captive lemurs at 11 zoological institutions in the United States. In Madagascar, 98 aerobic bacteria samples and 99 parasite samples were collected from eight sites chosen to cover a variety of populations across the species range. Identical collection, preservation and lab techniques were used for captiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 30 publications
3
25
1
1
Order By: Relevance
“…Altered gut immunity may allow for opportunistic microbes to colonize the guts of toxin-exposed animals, thus increasing species richness and altering microbial community structure. First, the gut microbiota can vary between animals in both nature and captivity [34][35][36]; thus, it would be interesting to see whether differences similar to the present study are also found between pristine and contaminated sites in the wild. Similarly, the genus Fusobacterium comprised a significant proportion of the microbial community of PCB-treated frogs, but not any other group studied.…”
Section: Discussionsupporting
confidence: 50%
“…Altered gut immunity may allow for opportunistic microbes to colonize the guts of toxin-exposed animals, thus increasing species richness and altering microbial community structure. First, the gut microbiota can vary between animals in both nature and captivity [34][35][36]; thus, it would be interesting to see whether differences similar to the present study are also found between pristine and contaminated sites in the wild. Similarly, the genus Fusobacterium comprised a significant proportion of the microbial community of PCB-treated frogs, but not any other group studied.…”
Section: Discussionsupporting
confidence: 50%
“…A study carried out in a zoo in Kenya on gastrointestinal parasites in primates obtained higher prevalence of helminthes (64.4%) compared to protozoa (17.1%), while another research conducted in the Zoological Gardens of Belgium on captive primates, found a higher prevalence of nematodes (36.5%) (Goossens et al 2005;Munene et al 1998). The clear differences are probably due to different types of management and housing, to the periods in which the studies were carried out but also to the use of different diagnostic techniques, as test properties vary significantly, particularly the sensitivity (Villers et al 2008). A study on ruminants at the Dublin zoo (Ireland) found a prevalence of positive animals to gastrointestinal nematodes and in particular to Trichuris spp.…”
Section: Discussionmentioning
confidence: 96%
“…Conspecific hosts have been shown to display dissimilarities when sampled from captive and wild environments (e.g. Uenishi et al ., ; Scupham et al ., ; Villers et al ., ; Xenoulis et al ., ; Nakamura et al ., ), although this has rarely been demonstrated in mammals, and this is the first study to identify this difference in marine seals. Dietary items can drive differences in the gut microbiota through the introduction of OTUs associated with prey.…”
Section: Discussionmentioning
confidence: 98%
“…Ley and colleagues () in their study on numerous terrestrial mammals, concluded that bacterial composition in the gut was generally more similar among conspecific hosts than among hosts of different species, regardless of whether they were from a captive or wild environment. A few studies have observed considerable differences between wild and captive individuals, but among mammals, these have been limited to primate species (Uenishi et al ., ; Villers et al ., ; Nakamura et al ., ), while several other studies have investigated such questions in birds (Scupham et al ., ; Xenoulis et al ., ; Wienemann et al ., ) and fish (Dhanasiri et al ., ).…”
Section: Introductionmentioning
confidence: 99%